Attraction Effects in Honorific Agreement in Korean - Kwon, Nayoung; Sturt, Patrick (Frontiers in Psychology, 2016)
Previous studies have suggested that sentence processing is mediated by content-addressable direct retrieval processes (McElree, 2000; McElree, Foraker, & Dyer, 2003). However, the memory retrieval processes may differ as a function of the type of dependency. For example, while many studies have reported facilitatory intrusion effects associated with a structurally illicit antecedent during the processing of subject-verb number or person agreement and negative polarity items (Dillon, Mishler, Sloggett, & Phillips, 2013; Pearlmutter, Garnsey & Bock, 1999; Xiang, Dillon, & Phillips, 2009), studies investigating reflexives have not found consistent evidence of intrusion effects (Parker & Lago, & Phillips, 2015; Sturt & Kwon, 2015; cf. Nicol & Swinney, 1989; Sturt, 2003). Similarly, the memory retrieval processes could be also sensitive to cross-linguistic differences (cf. Lago, Shalom, Sigman, Lau & Phillips, 2015). We report one self-paced reading experiment and one eye-tracking experiment that examine the processing of subject-verb honorific agreement, a dependency that is different from those that have been studied to date, in Korean, a typologically different language from those previously studied. The overall results suggest that the retrieval processes underlying the processing of subject-verb honorific agreement in Korean are susceptible to facilitatory intrusion effects from a structurally illicit but feature-matching subject, with a pattern that is similar to subject-verb agreement in English. In addition, the attraction effect was not limited to the ungrammatical sentences but was also found in grammatical sentences. The clear attraction effect in the grammatical sentences suggest that the attraction effect does not solely arise as the result of an error-driven process (cf. Wagers, Lau & Phillips, 2009), but is likely also to result from general mechanisms of retrieval processes of activating of potential items in memory (Vasishth, Brüssow, Lewis, & Drenhaus, 2008).